PENGARUH KEBIJAKAN DEVIDEN, PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DIBURSA EFEK INDONESIA - Wulandari, Rini; Prima, Argo Putra (SCIENTIA JOURNAL, 2019)
This research was conducted aimed at testing and analyzing the effect on Deviden Policy, profitability and solvency on manufacturing componies in the plastik and packaging sectors listed on the Indonesian Stock Exchange period 2013-2017. The type of data used was purposive sampling and the number of samples used was 7 plastic and packaging companies. Devidend policy variables, profitbility and solvency as independent variables, stock princes as the dependent variable. This data collection is done by observing the financial statements of plastik ang packanging componies on the Indonesian Stock Exchange. The result of classical assumption test show normal distribution data. The result of study prove that dividend policy partially does not have significant effect on stock princes, profitability has a significant effect on stock prices and solvency has a significant effect on stock prices. Dividend policy, profitability, and solvency simultaneously have a significant effect on stock prices in plastik and packaging componies listed on the stock exchange.